Development of Nursing Supervision Model of Emergency Surgical Nurse Worked After–hours at Department of Operating Room Nursing, Srinagarind Hospital - Sareeporn, Onura; Dapha, Sompratthana (Medical Journal of Sakon Nakhon Hospital, 2024)
This research aimed to develop the nursing supervision model of emergency surgical nurse worked after–hours at department of operating room nursing, Srinagarind hospital. The target groups were 16 supervisors and and 16 supervisees. The study was conducted from March 17, to June 10, 2022. The research process consisted of 4 steps as follows: 1) situation analysis, 2) design and development of the nursing supervision model, 3) implementation of the nursing supervision model, and 4) assessment of the nursing supervision model. The research tools were 1) the competency assessment for emergency surgical nurse worked after–hours with the content validity of 0.99. The Cronbach’s alpha coefficient was 0.98 and 2) the behavior observation record. Data were analyzed using statistics, frequency, percentage, mean and paired t–test. The study revealed that the developed nursing supervision model of emergency surgical nurse worked after–hours at department of operating room nursing, Srinagarind hospital consisted of 1) the system or process for supervision of the emergency surgical nurse worked after–hours called TKSA model, Teamwork (T), Knowledge (K), Skill (S) and Attitude (A) and 2) the nursing supervision process of emergency surgical nurse worked after–hours according to the 3 phases of GROW model, preoperative, intraoperative and postoperative nursing. In addition, after the implementation of developed supervision model, the average competency score of nurses receiving supervision was statistically significant increased from 217.94 (S.D. = 25.41) to 249.19 (S.D. = 31.65) (p < 0.05). The outcomes of service recipients using the nursing supervision model of emergency surgical nurses worked after–hours at department of operating room nursing, Srinagarind hospital should be further studied.